Pengaruh Penggunaan Brand Ambassador Nicholas Saputra Terhadap Citra Brand Kanzler (Survei Pada Followers Akun Instagram @Nicholassaputra) - Nazilah Nazilah; Iin Soraya; Sari Ekowati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The purpose of using brand ambassadors is one way for a company to shape an image and influence society. This research was aimed at finding out and measuring the influence of brand ambassadors on image. The theory used in this research is stimulus response theory. And the method used is a survey method with a quantitative approach. Data collection was carried out by distributing questionnaires to 200 respondents who came from followers of the Instagram account @nicholassaputra. This research aims to find out how much influence the use of brand ambassadors has on image. The results of this research show that there is an influence of the use of brand ambassadors on image.